Investigation of Manufacturability and Efficiency of Micro Channels with Different Geometries Produced by Direct Metal Laser Sintering - Çalışkan, Cemal İrfan; Coşkun, Mert; Özer, Gökhan; Koç, Ebubekir; Vurkır, Turgut Azer; Yöndem, Gökay (Springer, 2021)
Manufacturability without supports in design studies for additive manufacturing (AM) brings many advantages such as time, cost, part surface quality, and design freedom. It is thought that the geometries that can be produced without support will help the more widespread use of AMtechnologies. In this study, the unsupported manufacturability and efficiency research of conformal cooling channel (CCC) geometries created in cylindrical, wide oval, drop, hexagonal, narrow oval, and pentagonal cross-sections were conducted in the direct metal laser sintering (DMLS) system. The study offers innovation in terms of showing the usability of different channel geometries in CCC applications. The study shows that the pentagon form has the most efficient cooling capacity among the comparatively handled geometries. The results are obtained by a computational fluid dynamics (CFD) analysis study on computer-aided design (CAD) data of the actual state channel geometry obtained by CAD and postproduction micro-CT scanning of the design and presented in tables. This research shows that the production-induced sagging problem affects the flow by narrowing the channel hydraulic diameter in channel geometries produced without CCC supports.
Keywords: Conformal Cooling Channels; Microchannels; Additive Manufacturing; Direct Metal Laser Sintering